The Relationship Between Religion and Science: Perspectives from Islamic and Western Philosophy - Maspuroh Maspuroh; Siti Latifah; Siti Mariam; Fauzan Abdul Aziz (Penerbit Hellow Pustaka, 2026)
This article comparatively analyzes the relationship between religion and science through the lens of Islamic philosophy and Western philosophy. Science and religion, although often considered to have separate domains (empirical-rational versus revelation-belief), both strive to achieve truth. Historically, Islamic philosophy has tended to favor an integration-complementary model, viewing the universe and revelation as